Changing dynamics of renewable energy investments ecosystem: A scientometrics analysis - Rajesh Mohnot; Ilhan Ozturk; Aqila Rafiuddin; Gyanendra Singh Sisodia; Vivek Kumar Singh (Innovation and Green Development)
Renewable energy investments have undergone significant changes over the last two decades, largely influenced by the United Nations' sustainable development goals (SDGs), particularly those addressing climate change and the global demand for sustainable energy solutions. While significant progress has been made, persistent investment gaps and pronounced geographical disparities continue to pose challenges. The primary aim of this study is to assess the evolution and trajectory of research in the field of renewable energy investments, with a view to informing effective policy-making and strategic planning. The study employed a scientometric analysis covering the period from 2000 to 2024. An initial dataset of 20,141 documents was retrieved from the Scopus database. Using the PRISMA methodology, the dataset was refined and filtered down to 15,298 relevant publications. VOSviewer and Bibliometrix were then utilized for visualization and analytical mapping. These tools enabled a detailed examination of research patterns, thematic developments, and scholarly networks within the field. The analysis explores the dynamics of renewable energy investment research, offering a global perspective on strategies, policy instruments, and regulatory frameworks across different regions. In addition, the content analysis yields key insights into policy-relevant factors, investment evaluation techniques, the role of public-private partnerships (PPPs), and emerging economic and investment trends. This study makes a valuable contribution to the existing literature by serving as a reference point for understanding current trends and developments in renewable energy investment, while also offering insights into future research directions in the field.